Role of GSTM1 and GSTT1 polymorphism: Susceptibility to hypertension in Arabs residing in UAE - Khan, Gazala Afreen; Mahmood, Sidra Mohammed Al; Issam, Alaa; Samir, Rasha (International Journal of Innovative Research and Scientific Studies, 2025)
Hypertension is a multifactorial condition influenced by both genetic predisposition and environmental factors. Oxidative stress has been identified as a key contributor to the pathogenesis of hypertension. The present study aims to investigate the role of Glutathione-S-Transferase (GST) genes, specifically GSTM1 and GSTT1, in hypertensive patients from the Arab population residing in the United Arab Emirates. The study focuses on identifying the presence of these genes and genotyping null alleles to assess their potential association with hypertension risk. A cohort of 20 hypertensive patients was selected for genetic analysis using polymerase chain reaction (PCR) with specific primers. The presence and null alleles of the GSTM1 and GSTT1 genes were assessed and compared with age- and sex-matched control subjects. The data were statistically analyzed to determine the prevalence of null genotypes in hypertensive individuals versus the control group. Our analysis revealed that the GSTT1- and GSTM1-null genotypes were more prevalent in hypertensive patients (25%) compared to the control group (10%), although the difference did not reach statistical significance (p=0.172). These findings suggest a potential association between GST gene deletions and increased susceptibility to hypertension. The results indicate a possible link between GSTT1- and GSTM1-null genotypes and hypertension risk, supporting the role of oxidative stress-related genetic factors in disease development. However, due to the limited sample size, further research with larger cohorts is necessary to confirm these findings and explore additional genes involved in the antioxidant defense pathway. Understanding genetic predispositions related to oxidative stress may contribute to personalized hypertension risk assessments and targeted therapeutic strategies. Identifying genetic markers such as GSTT1 and GSTM1 null alleles could aid in early detection and the development of antioxidant-based interventions to mitigate hypertension risk in susceptible populations.